2019
DOI: 10.1111/1759-7714.13022
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of primary prophylactic pegylated‐granulocyte‐colony stimulating factor after the administration of ramucirumab plus docetaxel in patients with previously treated non‐small cell lung cancer

Abstract: Whether primary prophylactic pegylated‐granulocyte‐colony stimulating factor (PEG‐G‐CSF) should be administered immediately after the initiation of ramucirumab plus docetaxel (DR) to prevent the occurrence of febrile neutropenia (FN) is unclear. Our retrospective study aimed to elucidate whether PEG‐G‐CSF could control the occurrence of FN as a result of DR in patients with previously treated non‐small‐cell lung cancer. Thirty‐three patients with previously treated non‐small‐cell lung cancer who had received D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…Furthermore, in the JVCG trial, patients aged 75 years and older were rarely enrolled, resulting in a lack of clinical trial data for older patients. In recent retrospective studies which included some patients aged 75 years and older treated with RAM+DOC, there were no instances of FN after receiving prophylactic PEG‐G‐CSF support, whereas FN developed in patients not receiving PEG‐G‐CSF . In consideration of our results, the administration of PEG‐G‐CSF seemed to be essential therapy for RAM+DOC, especially in older patients.…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, in the JVCG trial, patients aged 75 years and older were rarely enrolled, resulting in a lack of clinical trial data for older patients. In recent retrospective studies which included some patients aged 75 years and older treated with RAM+DOC, there were no instances of FN after receiving prophylactic PEG‐G‐CSF support, whereas FN developed in patients not receiving PEG‐G‐CSF . In consideration of our results, the administration of PEG‐G‐CSF seemed to be essential therapy for RAM+DOC, especially in older patients.…”
Section: Discussionsupporting
confidence: 53%
“…At present, rhG-CSF and PEG-rhG-CSF are routinely used in antitumor adjuvant therapy, and PEG-rhG-CSF has shown more strengths. A large number of domestic and international studies have confirmed that PEG-rhG-CSF has similar efficacy to rhG-CSF but has superior safety in the prophylactic treatment of chemotherapy-induced non-myeloid-derived neutropenia [ 20 – 24 ]. RhG-CSF requires daily administration because of its short half-life [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients treated with G-CSF had reduced all-cause mortality. Atsuto Mouri performed a retrospective study of 33 patients with non-small-cell lung cancer (NSCLC) who had previously developed FN, and 29 patients received PEG-x’rhG-CSF prophylactically at the start of the next cycle of chemotherapy [ 20 ]. The median PFS and OS times for patients treated with and without PEG-rhG-CSF prophylactically were 177 and 163 days (PFS; P = 0.20), 628 days and 274 days (OS; P = 0.13), respectively, which are similar to the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…At present, rhG-CSF and PEG-rhG-CSF are routinely used in antitumor adjuvant therapy, and PEG-rhG-CSF has shown more strengths. A large number of domestic and international studies have con rmed that PEG-rhG-CSF has similar e cacy to rhG-CSF but has superior safety in the prophylactic treatment of chemotherapy-induced non-myeloidderived neutropenia [20][21][22][23][24]. RhG-CSF requires daily administration because of its short half-life [25][26][27].…”
Section: Discussionmentioning
confidence: 99%